Influência da preparação metalográfica e das condições de aquisição das imagens na quantificação automática de fases secundárias - Cleiton Carvalho Silva (2011)
In this work, the influence of the metallographic preparation and the image acquisition conditions on the quantification of secondary phases by a multilayer perceptron neural network was investigated. The images were obtained by scanning electron microscopy (SEM) from Ni-based superalloy coatings on C-Mn steel deposited by gas tungsten arc welding (GTAW) cold wire process. The results showed that excessive chemical etching of the microstructure (inadequate metallographic preparation) and/or inadequate brightness and contrast adjustment during the SEM image acquisitions interfere in the segmentation results and consequently on the secondary phase quantifications.